2005
DOI: 10.4067/s0717-95022005000300006
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of Mensuration to Avaliation of Indicators of Somatic Development of Wistar Rats

Abstract: SUMMARY:Evaluations of weight and cephalic perimeter are very used to study the growth and development in human beings. Similar measures, called murinometrics, have been an efficient resource to study the effects of nutritional and pharmacologic manipulations on the somatic development in rat. The aim of this study is to describe a method of evaluation which offers a higher accuracy in the collect of data in the study of somatic development in Wistar rat. Measurements were realized in latero-lateral axis of sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…The lack of nutrients and/or energy in developing organisms is usually demonstrated by growth deficit. 3,25 The diet used in our study also results in adverse consequences similar to those observed in the low-protein model. These findings have important implications for the optimal use of protein which is based on its quality and quantity along with an adequate energy intake ( protein:energy rate).…”
Section: Rd 3 (2-3) 3 (3-4) 3 (3-4) 3 (3-3) Vpsupporting
confidence: 56%
See 2 more Smart Citations
“…The lack of nutrients and/or energy in developing organisms is usually demonstrated by growth deficit. 3,25 The diet used in our study also results in adverse consequences similar to those observed in the low-protein model. These findings have important implications for the optimal use of protein which is based on its quality and quantity along with an adequate energy intake ( protein:energy rate).…”
Section: Rd 3 (2-3) 3 (3-4) 3 (3-4) 3 (3-3) Vpsupporting
confidence: 56%
“…Measurement of somatic growth 25 during lactation (tail length (TL), lateral-lateral axis of the skull (LLAS), anterior-posterior axis of the skull (APAS), and longitudinal axis (LA)) was performed every 3 days using a Stainless Hardened (Jomarca, Brazil) digital caliper with an accuracy of 0.01 mm from postnatal day 1 to 21. 25 Daily measurements of reflex maturation during lactation and characterized according to the protocol of Fox 26 is shown in Chart 1: recovery position, vibrissae placing (VP), cliff aversion (CA), negative geotaxis (NG), auditory startle response (AS), and free-fall righting (FR). For each reflex, the day of consolidation of its response was recorded, which was considered as the first day of the sequence of three consecutive days of a fullblown reflex response.…”
Section: Litter's Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific rate of weight gain was calculated employing the formula SWG = [(weight at day 21-weight at day 1)/ (weight at day 1 9 total number of days) [24]. Measurements of tail length (distance from the tip to the base of the tail), latero-lateral axis of the skull (distance between the ear holes) and the length of the anteroposterior axis of the skull (distance between the muzzle and head-neck joint) were obtained using digital calipers (Starrett Ò ), with an accuracy of 0.01 mm [25].…”
Section: Analysis Of Somatic Growthmentioning
confidence: 99%
“…However, it was observed some difficulty to establish more accurate parameters in the collect of data in our studies. In order to find more objective standard for the measurement of indicators of somatic development it was proposed the protocol of Silva et al (2005). The protocol considers the suitable use of the scapus of the pachymeter, suggesting the use of an instrument with better degree of accuracy and defining anatomic points as bases for the measurements.…”
Section: Introductionmentioning
confidence: 99%